First characterization of somatic proteins of trematodes of the family Paramphistomidae by SDS PAGE isolated from cattle from the Cajamarca region, Peru - Fernandez Mendoza, Charito Jennyfer (2026)
ABSTRACT Background: Paramphistomosis is a gastrointestinal parasitic disease of worldwide distribution, with higher prevalence in tropical and subtropical regions. Its biological cycle has a chronic phase caused by adult trematodes that adhere to the rumen mucosa and a highly pathogenic phase caused by immature trematodes, which induce acute parasitic gastroenteritis. Studies related to the parasite are very scarce in the region of Cajamarca, Peru, regarding the characterisation of antigenic proteins, considering that this parasitosis is endemic and has emerging characteristics. Aim: The study aimed to characterise somatic proteins of adult forms of Paramphistomidae in cattle by electrophoresis, Sodium dodecyl sulphate-polyacrylamide gel electrophoresis. Methods: For this purpose, 630 adult parasites were collected from the rumen and reticulum of cattle from the processing centre of Cajamarca, Peru. Results: The number of protein bands in the paramphistomid somatic crude extract was variable depending on the concentration of the protein analyzed. Thus, concentration 2 showed the highest number of protein bands (21 bands) with molecular weights (MW) within a variable range of 15 kDa–119 kDa. The results of ITS-2 gene sequencing, after alignment in NCBI’s Basic Local Alignment Search Tool of the obtained consensus sequences, show 100% similarity to sequences belonging to the species Calicophoron microbothrioides. Conclusion: Twenty-one protein bands from the somatic extract were characterized. The MWs of these bands ranged from 15 kDa to 119 kDa. This study may help carry out alternative control programmes, such as developing vaccines, choice of appropriate drugs due to the therapeutic failures expressed by this parasite. In addition, molecular identification based on ITS-2 gene sequencing revealed a 100% sequence similarity with Calicophoron microbothrioides.